Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 233: 17



Work Step by Step

Using $a^{m}\times a^{n}=a^{m+n}$, we obtain: $(3x^{2}y^{3})(-5xy^{4})$ =$(3\times-5)\times(x^{2} \times x)\times(y^{3}\times y^{4})$ =$(-15)\times(x^{2+1})\times(y^{3+4})$ =$(-15)\times(x^{3})\times(y^{7})$ =$-15x^{3}y^{7}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.